Pregnancy among unmarried women in a tertiary centre in Pahang, Malaysia - Mustafa, Kamarul Bahyah; Abd. Wahab, Noraziana; Sidek, A. A; Awang, Mokhtar; Abdullah, Suhaiza; Ibrahim, N. (Elsevier Ireland Ltd., 2012)
Objective: The study was aimed at obtaining sociodemographic data of unmarried women who delivered in the centre. The information includes age, education level, parental status, substance abuse and previous sexual abuse. Setting: Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia. Methods: This one year prospective study was conducted from 1 August 2010 until 31 July 2011 by identifying the women upon admission to this centre for delivery. They were interviewed using a standard guided questionnaire and conducted by a dedicated coresearcher. All unmarried pregnant women who came for delivery in this centre were included unless they refused. Results: During the study period, out of 9994 women who came for deliveries, 121 women were identified as unmarried, and were recruited. The youngest maternal age at delivery was 13, and the oldest was 36 with a mean age of 21.6 years. 31.4% were teenagers. Only 16% of patients have the benefit of higher education beyond their primary and secondary school, and 2.5% has never had any formal education. 36.3% of the women has their parents either divorced or widowed/widower. With regards to substance abuse, 31.4% of the women were either smoker or ex smoker, only 7.5% have ever consumed alcohol, and none admitted to ever use any recreational drugs. 90.9% of the women became pregnant after sexual debut with either their boyfriend or their fiance´e, and the other 9.1% either had the sexual encounter with someone other than the two mentioned, or did not know personally their sexual partner. 8.3% has prior history of being sexually assaulted. Ninety-two patients (76%) never used any contraceptive method despite majority of them (85.1%) were aware of the danger of sexually transmitted disease. Seventy-five percent of them were either unbooked or late booker. Of all the patients, 54 (45.8%) were not aware of availability of support groups. Conclusion: Single unmarried women are usually associated with poor background history, poor antenatal check up, substance abuse, and other social ills. This study has managed to identify certain possible background factors of these women in our society that may be addressed in order to improve the antenatal and postnatal care of the mother and babies in the future, as well as the social ills in general. This is important in this era of moral decadence.